Measuring EFL students’ self-efficacy levels in online learning (Englisia : Journal of Language, Education, and Humanities, 2023)
The rapid development of technology and the integration of technology into the education system have made several educational institutions begin to introduce and begin to apply it in their teaching and learning processes, one of which is by applying distance/online/remote learning methods that are considered flexible and convenience. The purpose of this study was to measure the level of self-efficacy that EFL students in higher education have regarding the use of online learning methods in their teaching and learning activities. The data in this study were taken through an online survey technique of 60 higher education EFL students. The instrument used is Self-Efficacy for Online Learning (SeQoL) which contains 20 statements with 3-point Likert-type scale. The findings in this study found that the level EFL learner self-efficacy in online learning was in moderate level (M= 2.22; SD= .59). Based on this result, EFL students need to adapt more to online learning methods so that they are able to master online learning experiences to get high self-efficacy.
Keywords: Self-Efficacy; EFL students; online learning